Microbiological Spectrum and Antibiotics Sensitivity Pattern of Chronic Suppurative Otitis Media (CSOM) Patients: A Prospective Study from a Tertiary Care Hospital - Abdul Manan Khan, Aria Masoom, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: CSOM is a fatal condition because of its propensity for intracranial extension. Overuse of antibiotics has resulted in resistance among bacteria. Objective: The aim of the current study was to find out the microbiological spectrum and antibiotics susceptibility patterns in tertiary care hospital. Material and method: The current prospective study was conducted at the Department of ENT, Bolan Medical College / Complex Hospital, Quetta from February 2022 to February 2023 after taking approval from the research committee of the institute. A total of 118 individuals of both gender and different age groups with Chronic Suppurative Otitis Media were included. A pus sample was taken from both ears of individuals using an aseptic swab for microscopic analysis and bacterial culture. Following their inoculation into various media all of the samples were maintained in an aerobic environment at 37°C for 18 to 20 hours. For the identification of bacteria microscopy, gram staining and biochemical tests such as urease, citrate, and triple sugar iron were performed. Modified Kirby Bauer disc diffusion technique was used to find out the antibiotic susceptibility pattern of bacteria. We classified the bacteria as either susceptible or resistant based on the CLSI standards. Both clinical and demographic information about the patient was gathered using a well-structured questionnaire. The numbers (n) and percentages (%) were used to represent quantitative variables. For evaluating the data collected, SPSS version 12 was used. Results: A total of 118 individuals were examined in this study out of which 60% were female and 40% were male. Out of the total samples 85% showed growth and 15% were culture negative. The most prevalent bacteria isolated was Pseudomonas aeruginosa 39% followed by S.aureus 25.4%, Proteus species 14.7% S. saprophyticus 7.8% Providencia 4(3.9%), Citrobacter3.9%, Serratia marcescens 1.9%, Enterobacter species 1.9% E. coli 1.9%. Antibiogram of isolated bacteria showed that S. aureus was mostly sensitive to Linezolid 82% and Vancomycin 78%. Gram-negative bacteria exhibited a wide range of sensitivity, with 52% -100% susceptibility to imipenem and Meropenem. Conclusion: The current study concluded that the most prevalent bacteria isolated from chronic suppurative otitis media individuals were Pseudomonas aeruginosa followed by s.aureus. Vancomycin and Linezolid were more effective against gram positive bacteria and carbapenem, cefoperazone with sulbactam, and piperacillin/tazobactam were effective against gram negative bacteria. Keywords: Microbiological Spectrum; Antibiotics Sensitivity Pattern; Chronic Suppurative Otitis Media